EFFECTS OF SPECIFIC VOLLEYBALL TRAINING ON SELECTED SKILL PERFORMANCE VARIABLES AMONG WOMEN VOLLEYBALL PLAYERS - S. Rajesh,; Dr. S. Veeramani, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The point of the present study was to find out the effect of specific volleyball training on selected skill performance variables among women volleyball players. To achieve the purpose of the study women volleyball players were selected from Government Arts and Science college of Mayiladuthurai District, Tamil Nadu, India. The subject’s age ranges from 18 to 25 years. The selected subjects were divided into two equal groups consists of 15 volleyball women each namely experimental group and control group. The experimental group underwent a specific volleyball skill training programme for twelve weeks. The control group was not taking part in any training during the course of the study. Spiking, Service and Passing was taken as criterion variable in this study. Pre-test was taken before the training period and post- test was measured immediately after the twelve-week training period. Statistical technique‘t’ ratio was used to analyze the means of the pre-test and post test data of experimental group and control group. The results revealed that there was a significant difference found on the criterion variables. The difference is found due to specific volleyball skill training given to the experimental group on Spiking, Service and Passing when compared to control group.